The Effect of Organizational Culture on Employee Performance Mediated by Person-Organization Fit, Organization Commitment, and Employee Engagement in the Millennial Generation in Companies Badan Usaha Milik Negara - Basuki, Rahmanto; S Panggabean, Mutiara; Warsindah, Lucy (International Journal of Science, Technology & Management, 2024)
This study was conducted to determine the perceptions of BUMN employees who are categorized as millennials about the influence of organizational culture on Employee performance, with an interesting indicator to study, namely Counter Productive Work Behaviour. As well as whether a Person's organizational fit, organizational commitment, and employee engagement mediate the influence of organizational culture on employee performance. The research method used is a descriptive method with a quantitative approach. The data collection method used is by distributing questionnaires through the Google Forms link. The questionnaire was distributed to each cluster for 4 weeks and assisted by the administration of each BUMN cluster. Respondents who filled out the link in the google form were 403 but those who entered the appropriate criteria were 366. The data was obtained and analyzed using Structural Equation Modelling (SEM). The results of research conducted on 10 BUMN clusters aimed at analyzing the effect of Organisation Culture on Employee Performance through Person Organisation Fit, Organisation Commitment, and Employee Engagement where most of the respondents were female (86%) with a Bachelor's degree (54%), and executors or low management (81%), found that: There is a positive influence of corporate culture on employee performance, person-organization fit, and employee engagement but no effect on organization commitment.There is a positive influence on person.